2019
DOI: 10.1111/1750-3841.14466
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Peptide Profile Consistency and Safety of Collagen Hydrolysates as Quality Attributes

Abstract: Collagen hydrolysates are dietary supplements used for nutritional and medical purposes. They are complex mixtures of low‐molecular‐weight peptides obtained from the enzymatic hydrolysis of collagen, which provide intrinsic batch‐to‐batch heterogeneity. In consequence, the quality of these products, which is related to the reproducibility of their mass distribution pattern, should be addressed. Here, we propose an analytical approach to determine the peptide pattern as a quality attribute of Colagenart®, a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Baar et al [23] showed that AAs present in high amounts in collagen (glycine, proline, lysine, hydroxyproline and hydroxylysine) combined with vitamin C could improve collagen synthesis in a tissue-engineered ligament model. Similar findings were reported by de Paz-Lugo et al [20], who found that glycine and proline enhanced type II collagen synthesis in bovine articular chondrocytes, suggesting that increased consumption of these AAs could be beneficial for the regeneration of the articular cartilage matrix. Oesser et al [24] investigated the absorption of gelatin hydrolysate and its subsequent tissue distribution in mice.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Baar et al [23] showed that AAs present in high amounts in collagen (glycine, proline, lysine, hydroxyproline and hydroxylysine) combined with vitamin C could improve collagen synthesis in a tissue-engineered ligament model. Similar findings were reported by de Paz-Lugo et al [20], who found that glycine and proline enhanced type II collagen synthesis in bovine articular chondrocytes, suggesting that increased consumption of these AAs could be beneficial for the regeneration of the articular cartilage matrix. Oesser et al [24] investigated the absorption of gelatin hydrolysate and its subsequent tissue distribution in mice.…”
Section: Discussionsupporting
confidence: 90%
“…Plasma concentrations of glycine and proline peaked 60 and 90 min after intake of EHC and NC, respectively. Previous studies have reported similar findings with a peak in hydroxyproline after 120 min and a subsequent decrease to half the maximum after four hours following consumption of hydrolyzed collagen [20,27].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Human consumption of dietary supplements such as hydrolyzed collagen has been deemed to be safe. Lopez-Morales et al [103] conducted a detailed experimental work to characterize HC with different techniques such as ultraviolet detection (SEC-UV), reverse phase chromatography coupled to electrospray ionization ion mobility quadrupole time-of-flight spectrometer (RP-HPLCESI-IMS-QTOF), and shaped-pulse water-suppression one (1D)-and two-dimensional (2D) proton nuclear magnetic resonance spectra. Safety and toxicity of HC were assessed in vitro by using CaCo-2 and HepG2 cell lines.…”
Section: Absorption Of Hc Into the Blood Torrentmentioning
confidence: 99%
“…Nowadays, IMS applications in food composition cover a wide variety of substances (e.g., lipids, peptides, phenolic compounds, terpenes, etc.) [44,45,46,47], including allergens [48], and samples (e.g., flours, olive oil, mushrooms, etc.) [48,49,50].…”
Section: Applications Of Ims In Food Analysismentioning
confidence: 99%